The Relationship between Age and Maternity Parity with Postterm Birth - Nadhifa Anwar Maulinda; Tutik Rusdyati (Universitas Airlangga, 2018)
Background: Postterm birth is one of the causes of death of babies (0-6 years old) in Indonesia by 2,80%. There were risk factors for postterm birth, namely age and maternity parity. Purpose: This study aimed to investigate the relationship between age, maternity parity with the postterm birth in mother and child hospital (RSIA) Arafah Anwar Medika Sukodono Sidoarjo district. Methods: The design of this observational study was cross-sectional. Data were obtained from medical record of 218 women delivering baby RSIA Arafah Anwar Medika in 2013. Respondents were selected through random sampling. Data were analyzed through fisher exact statistical analysis. Results: The most of the respondents were aged 20-35 years old (86,70%), with the risk of parity (91,70%), and without posterm (85,32%). However, the post-term pregnancy was found in respondents aged below 20 and above 35 years old (2,75%) also in respondents with parity risk (3,21%). Conclusion: There was no correlation between mother’s age and post-term pregnancy (p = 0,23; RR = 1,50; 95% CI = 0,68 < RR < 3,34). Meanwhile, the parity risk was correlate to post-term pregnancy (p = 0,01; RR = 3,11; 95% CI = 1,57 < RR < 6,17).